The Spectacle of Politics and Religion in the Contemporary Turkish Cinema - Thwaites Diken, Ebru (Springer International Publishing, 2018)
This book explores how politics, religion and cinema encounter and re-invent each other in contemporary Turkish cinema. It investigates their common origin-the spectacle, which each field views as an instrument of governmentality. The book analyses six recent internationally known Turkish films. Thwaites discusses how the cinematic nature of politics and religion unfold amidst the increasing media visibility of religion in contemporary Turkey. The chapters explore the relationship between art and religion, and compare religion and philosophy in their relation to truth, belief, and economy. Through close examination of these films, the author highlights the role of cinema in contemporary Turkey and at the heart of the religious paradigm.